2019
DOI: 10.14814/phy2.14251
|View full text |Cite
|
Sign up to set email alerts
|

Sex effects of dietary protein source and acid load on renal and bone status in thePahenu2mouse model of phenylketonuria

Abstract: The low‐phenylalanine (Phe) diet with amino acid (AA) medical foods is associated with low bone mineral density (BMD) and renal dysfunction in human phenylketonuria (PKU). Our objective was to determine if diets differing in dietary protein source and acid load alter bone and renal outcomes in Pah−/− and wild‐type (WT) mice. Female and male Pah−/− (Pahenu2/enu2) and WT littermates (C57BL/6 background) were fed high‐acid AA, buffered AA (BAA), glycomacropeptide (GMP), or high‐Phe casein diets from 3 to 24 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In this field, the research on the features of the GMP polypeptide has spanned in different directions to find that GMP can bind and inactivate toxins of E. coli and Vibrio cholerae [221], inhibit the adhesion of cariogenic bacteria [222], enhance zinc absorption [223], increase cytokine production [224] and decrease stimulation of T-helper1 lymphocytes in rats [225], and act as an anti-inflammatory in different models [226,227]. Among others, GMP has been studied for the control of satiety, although with conflicting results [228][229][230], for the effects on bone size and strength [231][232][233], and interestingly for its role as prebiotic. The latter is thought to be based on the fact that GMP shows a high degree of glycosylation that includes mucin-like oligosaccharide chains that contain sialic acid, galactose, and galactosamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this field, the research on the features of the GMP polypeptide has spanned in different directions to find that GMP can bind and inactivate toxins of E. coli and Vibrio cholerae [221], inhibit the adhesion of cariogenic bacteria [222], enhance zinc absorption [223], increase cytokine production [224] and decrease stimulation of T-helper1 lymphocytes in rats [225], and act as an anti-inflammatory in different models [226,227]. Among others, GMP has been studied for the control of satiety, although with conflicting results [228][229][230], for the effects on bone size and strength [231][232][233], and interestingly for its role as prebiotic. The latter is thought to be based on the fact that GMP shows a high degree of glycosylation that includes mucin-like oligosaccharide chains that contain sialic acid, galactose, and galactosamine.…”
Section: Discussionmentioning
confidence: 99%
“…inflammatory in different models [226,227]. Among others, GMP has been studied for the control of satiety, although with conflicting results [228][229][230], for the effects on bone size and strength [231][232][233], and interestingly for its role as prebiotic. The latter is thought to be based on the fact that GMP shows a high degree of glycosylation that includes mucin-like oligosaccharide chains that contain sialic acid, galactose, and galactosamine.…”
Section: Discussionmentioning
confidence: 99%
“…Hennermann and her colleagues detected impaired renal function, proteinuria, and arterial hypertension in ETPKU patients on a lifelong diet [27]. In a study performed with PKU mice models (Pah enu2 ), it was found that chronic ingestion of AAs had a negative effect on renal function, compared with natural protein intake from food [29].…”
Section: Discussionmentioning
confidence: 99%